On Certain Matrices of Bernoulli Numbers - Ruiming Zhang; Li-Chen Chen (Abstract and Applied Analysis)
In this work we compute the determinant and inverse matrices for a certain symmetric matrix of Rayleigh sums. As a special case we also obtain the determinants and inverses for the matrices of the Bernoulli numbers and related numbers.